Application of Bio P60 and Bio T10 Alone or in Combination Against Stem Rot of Pakcoy - Soesanto, Loekas; Hiban, Atsil; Suharti, Woro Sri (Yayasan Pertanian Tropika Indonesia (YPTI), 2019)
Application of Bio P60 and Bio T10 alone or in combination in suppressing stem rot of pakcoy and on pakcoy growth has been demonstrated. The research was carried out at the Plant Protection Laboratory and Screen House, Faculty of Agriculture, Jenderal Soedirman University. A split-plot design was used with application time (before and after inoculation of Sclerotium rolfsii) as main plot and Bio P60, Bio T10, and Bio P60 + Bio T10) as sub-plot. Observed variables were incubation period, disease intensity, crop height, number of leaves, and crop fresh weight. Results of the research showed that single and combined application of Bio T10 and Bio P60 did not differ in the suppression of stem-end rot in pakcoy. The combination of Bio T10 + Bio P60 was able to control the disease by delaying the incubation period and suppressing the disease intensity respectively by 37.48-39.16% and 54.77-6191% compared to controls. Combined Bio T10 + Bio P60 was able to improve plant height, number of leaves, and fresh weight of plants as 29.99-46.62, 24.39-35.07, and 71,17%, respectively, compared to controls. The results of this study suggest that the raw secondary metabolites of Bio P60 and Bio T10 either alone or in combination could be applied for the prevention or treatment of the diseases in pakcoy.